2021
DOI: 10.1159/000519897
|View full text |Cite
|
Sign up to set email alerts
|

Is JJ Ureteral Stenting Inferior to Percutaneous Nephrostomy as a Drainage Method in Emphysematous Pyelonephritis?

Abstract: <b><i>Introduction:</i></b> The aim of the study was to examine the efficacy of JJ stenting in comparison with percutaneous nephrostomy (PCN) as a drainage method in patients with emphysematous pyelonephritis (EPN). <b><i>Methods:</i></b> We retrospectively identified patients with EPN between January 2000 and January 2021. Platelet-to-leukocytic ratio (PLR) at the time of hospital admission and discharge, time taken to clear air locules and to normalize leukocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In a previous study, Elbaset et al [16] documented that higher air locules volume may be associated with different drainage methods failure (either PCD or ureteral stent) and poor clinical outcome [16]. In our The presence of hydronephrosis and urinary stasis provide the time and opportunity for bacteria to adhere to the urinary tract epithelium, multiply, and infect the host [16].…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…In a previous study, Elbaset et al [16] documented that higher air locules volume may be associated with different drainage methods failure (either PCD or ureteral stent) and poor clinical outcome [16]. In our The presence of hydronephrosis and urinary stasis provide the time and opportunity for bacteria to adhere to the urinary tract epithelium, multiply, and infect the host [16].…”
Section: Discussionmentioning
confidence: 60%
“…In a previous study, Elbaset et al [16] documented that higher air locules volume may be associated with different drainage methods failure (either PCD or ureteral stent) and poor clinical outcome [16]. In our The presence of hydronephrosis and urinary stasis provide the time and opportunity for bacteria to adhere to the urinary tract epithelium, multiply, and infect the host [16]. The presence of hydronephrosis increase the risk of gas chamber theory by increased the pelvicalyceal system pressure and compromised renal circulation with impaired gas transportation [6].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Leukocyte and platelets play an active role in the systemic inflammatory response to infection and antimicrobial host defense. Platelets support leucocytes in pathogen arrest and transmigration ( 18 ). Elbaset et al ( 19 ) found that lower platelet to leucocytic count ratio (PLR) is an independent simple predictor for sepsis and mortality in EPN patients.…”
Section: Discussionmentioning
confidence: 99%
“…The high glucose content in tissues provides a favorable environment for the gas-producing fermentation of bacteria, thus promoting the growth of bacteria, leading to renal parenchyma destruction and higher morbidity ( 1 , 8 ). Also, the high glucose content in tissues impairs leukocytic function and leads to higher incidence of sepsis ( 18 ). In our study, all cases were comorbid with diabetes mellitus, and had poor glycemic control at admission.…”
Section: Discussionmentioning
confidence: 99%